Komunikasi Pemasaran Offline to Digital (O2O) PT. Bank Aladin Syariah Tbk. - Husada, Safaruddin; Yunus, Ulani (Jurnal Pustaka Komunikasi, 2024)
This study investigates PT Bank Aladin Syariah Tbk's marketing communication strategy transitioning from online to offline (O2O) channels, aiming to enhance customer engagement. Employing qualitative descriptive methodology, data were collected through non-participant observation, literature review, and archival analysis, utilizing purposive sampling for key informant selection. Data analysis involved reduction, presentation, and verification. Findings reveal Bank Aladin's active utilization of digital promotional mix via social media platforms and partnership collaborations with Alfamart convenience stores, employing a co-branding strategy to maintain hard-selling approaches for customer acquisition and third-party funds. Moreover, Bank Aladin launched a Shariah-compliant banking application with user-friendly and seamless features, garnering 3.2 million downloads and over 1.7 million registered users since December 2022. This study underscores the efficacy of integrating online platforms and strategic partnerships in enhancing customer outreach and service delivery within the Islamic banking sector.